Comparison of Different Fixation Techniques of the Long Head of the Biceps Tendon in Superior Capsule Reconstruction for Irreparable Posterosuperior Rotator Cuff Tears: A Dynamic Biomechanical Evaluation. Issue 2 (February 2021) - Berthold, Daniel P.; Muench, Lukas N.; Dyrna, Felix; Scheiderer, Bastian; Obopilwe, Elifho; Cote, Mark P.; Krifter, Michael R.; Milano, Guiseppe; Bell, Ryan; Voss, Andreas; Imhoff, Andreas B.; Mazzocca, Augustus D.; et al.
Background: In the past decade, superior capsular reconstruction has emerged as a potential surgical approach in young patients with irreparable posterosuperior rotator cuff tears (RCT) and absence of severe degenerative changes. Recently, the use of locally available and biological viable autografts, such as the long head of the biceps tendon (LHBT) for SCR has emerged, with promising early results. Purpose/Hypothesis: The purpose of this study was to investigate the effect of using the LHBT for reconstruction of the superior capsule on shoulder kinematics, along with different fixation constructs in a dynamic biomechanical model. The authors hypothesized that each of the 3 proposed fixation techniques would restore native joint kinematics, including glenohumeral superior translation (ghST), maximum abduction angle (MAA), maximum cumulative deltoid force (cDF), and subacromial peak contact pressure (sCP). Study Design: Controlled laboratory study. Methods: Eight fresh-frozen cadaveric shoulders (mean age, 53.4 ± 14.2 years) were tested using a dynamic shoulder simulator. Each specimen underwent the following 5 conditions: (1) intact, (2) irreparable posterosuperior rotator cuff tear (psRCT), (3) V-shaped LHBT reconstruction, (4) box-shaped LHBT reconstruction, and (5) single-stranded LHBT reconstruction. MAA, ghST, cDF and sCP were assessed in each tested condition. Results: Each of the 3 LHBT techniques for reconstruction of the superior capsule significantly increased MAA while significantly decreasing ghST and cDF compared with the psRCT ( P < .001 and P < .001, respectively). Additionally, the V-shaped and box-shaped techniques significantly decreased sCP ( P = .009 and P = .016, respectively) compared with the psRCT. The V-shaped technique further showed a significantly increased MAA ( P < .001, respectively) and decreased cDF ( P = .042 and P = .039, respectively) when compared with the box-shaped and single-stranded techniques, as well as a significantly decreased ghST ( P = .027) when compared with the box-shaped technique. Conclusion: In a dynamic biomechanical cadaveric model, using the LHBT for reconstruction of the superior capsule improved shoulder function by preventing superior humeral migration, decreasing deltoid forces and sCP. As such, the development of rotator cuff tear arthropathy in patients with irreparable psRCTs could potentially be delayed. Clinical Relevance: Using a biologically viable and locally available LHBT autograft is a cost-effective, potentially time-saving, and technically feasible alternative for reconstruction of the superior capsule, which may result in favorable outcomes in irreparable psRCTs. Moreover, each of the 3 techniques restored native shoulder biomechanics, which may help improve shoulder function by preventing superior humeral head migration and the development of rotator cuff tear arthropathy in young patients with irreparable rotator cuff tears.